A Question of Perspective: Impact Assessment and the Perceived Costs and Benefits of New Regulations for SMEs. (February 2015) - Chittenden, Francis; Ambler, Tim
Regulation remains a contentious topic between small firms, policy makers, and scholars. Business lobbying organizations persistently claim that regulation acts as a deterrent to economic activity. In contrast, policy makers and some scholars have argued that regulation creates net benefits for society and so may have a modest positive impact on SMEs. This paper seeks to offer at least a partial explanation for these very different perspectives. Through studying the majority of UK Impact Assessments issued over the twelve years from 1998 to 2009 and relevant government publications, we find that differences in the objective decision-making criteria (algorithms and heuristics) of the parties involved provide at least a partial explanation of why their views appear irreconcilable. It is argued that both are acting rationally in pursuit of higher goals and are not simply 'gaming' in order to gain the greatest private advantage.